Cardiac resynchronization therapy via transvenous approach in a 2‐year‐old boy with a complete atrioventricular block after a tetralogy of Fallot repair. Issue 6 (9th September 2017) - Aoki, Hisaaki; Emi, Misugi; Inamura, Noboru; Iwai, Shigemitsu; Kayatani, Futoshi
Abstract: Cardiac resychronization therapy (CRT) was performed via transvenous approach in a 2‐year‐old boy with a tetralogy of Fallot and postoperative severe heart failure, and complete atrioventricular block treated with a dual‐chamber pacemaker. Epicardial leads were unavailable because of mediastinitis and the presence of severe bilateral pleural effusions requiring continuous drainage. There were no procedural complications. Biventricular pacing was significantly effective and both mediastinitis and pleural effusions recurred. The transvenous CRT was exchanged for an epicardial CRT after 4 months because of the possibility of a venous obstruction.